Pillars of Society - Ibsen, Henrik, 1828-1906; Sharp, R. Farquharson (Robert Farquharson), 1864-1945 (Salt Lake City, UT : Project Gutenberg, 2000)
"Pillars of Society" by Henrik Ibsen is a play written in 1877. Karsten Bernick is a respected businessman in a Norwegian coastal town, but his carefully constructed reputation faces collapse when figures from his past return after fifteen years. They know the truth about a scandal he allowed another man to take the blame for. Desperate to protect his secrets and social standing, Bernick makes increasingly dangerous choices that threaten both his family and his soul. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Pillars_of_Society
Release date is 2000-08-01
Produced by Martin Adamson. HTML version by Al Haines.
Keywords: Norwegian drama -- Translations into English; Businessmen -- Drama; Hypocrisy -- Drama; Norway -- Drama